Maternal cigarette smoking during pregnancy and offspring DNA methylation in midlife. Issue 2 (1st February 2018) - Tehranifar, Parisa; Wu, Hui-Chen; McDonald, Jasmine A.; Jasmine, Farzana; Santella, Regina M.; Gurvich, Irina; Flom, Julie D.; Terry, Mary Beth
ABSTRACT: Maternal smoking in pregnancy (MSP) has been associated with DNA methylation in specific CpG sites (CpGs) in infants and children. We investigated whether MSP, independent of own personal active smoking, was associated with midlife DNA methylation in CpGs that were previously identified in studies of MSP-DNA methylation in children. We used data on MSP collected from pregnant mothers of 89 adult women born in 1959–1964 and measured DNA methylation in blood (granulocytes) collected in 2001–2007 (mean age: 43 years). Seventeen CpGs were differentially methylated by MSP, with multiple CpGs mapping to CYP1A1, MYO1G, AHRR, and GFI1 . These associations were consistent in direction with prior studies (e.g., MSP associated with more and less methylation in AHRR and CYP1A1, respectively) and, with the exception of AHRR CpGs, were not substantially altered by adjustment for active smoking. These preliminary results confirm prior prospective reports that MSP influences the offspring DNA methylation, and extends the timeframe to midlife, and suggest that these effects may persist into adulthood, independently of active smoking.